Bifunctional metal-organic framework material based on pyridine tetracarboxylic acid ligand as well as preparation method and application of bifunctional metal-organic framework material
Through bifunctional metal-organic framework materials based on pyridine tetracarboxylic acid ligand, the problems of gas separation and heavy metal ion detection are solved, and efficient gas separation and high-sensitivity heavy metal ion detection are achieved.
Patent Information
- Application Number
- CN202411767935.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-04
AI Technical Summary
The prior art is difficult to effectively separate gases such as C2H2 and CO2, and traditional heavy metal ion detection methods are expensive and not easy to carry, so they cannot be tested in real time.
The material was prepared by solvothermal reaction using a bifunctional metal-organic framework material based on pyridine tetracarboxylic acid ligand, and its excellent gas adsorption and separation and heavy metal ion fluorescence detection performance.
It realizes efficient separation of mixed gases C2H2/CO2 and CO2/CH4, as well as high sensitivity detection of Fe3+, Cr2O72- and CrO42-, and the detection limit exceeds that of most MOFs materials.
Smart Images

Figure CN119751899A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of crystalline materials, and in particular relates to a bifunctional metal-organic framework material based on pyridinetetracarboxylic acid ligands. The present invention also relates to a preparation method of the bifunctional metal-organic framework material based on pyridinetetracarboxylic acid ligands. The present invention further relates to the application of the bifunctional metal-organic framework material based on pyridinetetracarboxylic acid ligands. Background Art
[0002] Acetylene (C2H2) is a very important chemical raw material. It releases a lot of heat when burned and can be used as welding fuel. The main source of C2H2 in industry is the thermal decomposition of natural gas. This process inevitably produces carbon dioxide (CO2). Therefore, it is necessary to separate the mixture of C2H2 and CO2 to obtain high-purity C2H2. In addition, the presence of CO2 in CH4 will not only sharply reduce the calorific value of combustion, but also cause serious corrosion to the transmission pipeline. Therefore, removing CO2 from natural gas has important industrial application value. Compared with inorganic porous materials, Metal-Organic Frameworks (MOFs) are considered to be promising gas adsorption and separation materials due to their large specific surface area and adjustable pore size.
[0003] On the other hand, with the progress of society, water pollution has become a topic of increasing concern. For example, wastewater discharged from the production of metallurgy and paint industries usually contains Cr2O7 2- 、CrO4 2- and Fe 3+ Heavy metal ions such as ions can have an impact on human health and the environment. At present, some methods for detecting heavy metal ions have been developed, including gas chromatography, atomic absorption spectroscopy and spectrophotometry. However, these methods are expensive and not easy to carry, and cannot be used for real-time detection. Therefore, it is necessary to develop some detection methods that are simple to operate and have a fast response speed. In recent years, it has been found that metal organic frameworks can be used as fluorescent sensors to solve the problems of traditional detection methods.
[0004] Therefore, pyridinetetracarboxylic acid (2,5-di-(3,5-dicarboxyphenyl))pyridine (H4L) was selected as the organic ligand, in which the polycarboxylic acid can provide more coordination sites and form more coordination modes, which is conducive to the formation of novel structures. At the same time, the pyridine ring can make the formed structure more stable, thereby showing excellent gas adsorption and separation and heavy metal ion detection performance. Summary of the invention
[0005] The object of the present invention is to provide a bifunctional metal-organic framework material based on pyridinetetracarboxylic acid ligands, which has excellent stability and can exhibit excellent gas adsorption and separation and heavy metal ion fluorescence detection performance.
[0006] Another object of the present invention is to provide a method for preparing a bifunctional metal-organic framework material based on pyridinetetracarboxylic acid ligands.
[0007] Another object of the present invention is to provide an application of a bifunctional metal-organic framework material based on pyridinetetracarboxylic acid ligands.
[0008] The first technical solution adopted by the present invention is: a bifunctional metal-organic framework material based on pyridine tetracarboxylic acid ligand, the chemical formula of which is {[Zn2(L)(5-ATZ)]·1.5DMF·H2O} n , L 4- It is a deprotonated organic ligand (2,5-di-(3,5-dicarboxyphenyl))pyridine.
[0009] The first technical solution of the present invention is also characterized in that: {[Zn2(L)(5-ATZ)]·1.5DMF·H2O} n The crystal structure belongs to the orthorhombic system. Imma Space group, unit cell parameters are: a = 19.038(14) Å, b = 26.520(19) Å, c = 17.040(12) Å, α = β = γ = 90°.
[0010] {[Zn2(L)(5-ATZ)]·1.5DMF·H2O} n One asymmetric unit contains a Zn 2+ ion, half ligand and half aminotetrazolyl; Zn1 and from three L 4- The four oxygen atoms of the ligand and the nitrogen atom on the aminotetrazolyl form a five-coordinated tetrahedral geometry; L 4- There are two coordination modes of carboxylic acid oxygen atoms in the ligand, μ1-η 1 and μ1-η 2 ; Two Zn1(Ⅱ) ions form a binuclear structural unit, each L 4- The ligand forms a three-dimensional framework structure with pores by connecting four nearby binuclear structural units.
[0011] The organic ligand (2,5-di-(3,5-dicarboxyphenyl))pyridine is a rigid linear structure, comprising four carboxylic acid functional groups and a pyridine nitrogen atom, and the four carboxylic acids are located at the meta position of the outer benzene ring.
[0012] The chemical formula of the organic ligand (2,5-di-(3,5-dicarboxyphenyl))pyridine is: .
[0013] The second technical solution adopted by the present invention is: a preparation method of a bifunctional metal-organic framework material based on pyridinetetracarboxylic acid ligand, in which an organic ligand (2,5-di-(3,5-dicarboxyphenyl))pyridine reacts with aminotetrazolyl and zinc nitrate hexahydrate in a mixed solution of N,N-dimethylformamide and nitric acid under sealed conditions to obtain colorless crystals through a solvothermal reaction.
[0014] The second technical solution of the present invention is also characterized in that: The molar ratio of the organic ligand (2,5-di-(3,5-dicarboxyphenyl))pyridine, aminotetrazole and zinc nitrate hexahydrate is 3:5:8, and every 0.04 mmol of zinc nitrate hexahydrate corresponds to 2-4 mL of N,N-dimethylformamide and 1-4 mL of nitric acid, wherein the concentration of nitric acid is 1 mL of HNO3 dissolved in 10 mL of distilled water.
[0015] The temperature of the solvent thermal reaction is 90 to 130°C, and the time is 24 to 60 hours.
[0016] The third technical solution adopted by the present invention is: the application of bifunctional metal-organic framework materials based on pyridinetetracarboxylic acid ligands, the bifunctional metal-organic framework materials based on pyridinetetracarboxylic acid ligands are used as materials for CO2 / CH4 and C2H2 / CO2 adsorption and separation, or as Fe in aqueous solution. 3+ 、Cr2O7 2- and CrO4 2- Highly sensitive fluorescent detection material.
[0017] The beneficial effects of the present invention are as follows: the bifunctional metal-organic framework material based on pyridinetetracarboxylic acid ligand and its preparation method and application have excellent stability and can exhibit excellent gas adsorption and separation and heavy metal ion fluorescence detection performance. The separation ratios of mixed gases C2H2 / CO2 and CO2 / CH4 are 5.32 and 17.2 respectively, and the separation ratios of Fe 3+ 、Cr2O7 2- and CrO4 2- The detection limit reached 10 -4 M, which exceeds most existing MOFs materials. The present invention opens up new design and synthesis prospects for novel linear pyridine tetracarboxylic acid ligand-based functional metal organic frameworks and can be used in gas pollution and water pollution. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 is a Zn(II) ion coordination environment diagram of the metal-organic framework of the present invention; Figure 2is a coordination geometry diagram of metal clusters and Zn(II) ions in the metal-organic framework of the present invention; Figure 3 L in the metal-organic framework of the present invention 4- Coordination pattern diagram of Figure 4 is a three-dimensional image of the metal-organic framework of the present invention; Figure 5 is the N2 adsorption isotherm of the metal-organic framework of the present invention at 77 K (the inset shows the pore size distribution); Figure 6 are the C2H2, CO2 and CH4 adsorption isotherms of the metal-organic framework of the present invention at 273 K and 298 K; Figure 7 is the separation ratio curve of the metal-organic framework of the present invention for CO2 / CH4 and C2H2 / CO2 at 298 K; Figure 8 is a histogram of the luminescence intensity of the metal-organic framework of the present invention in different cation solutions; Fig. 9 The metal-organic framework of the present invention has different concentrations of Fe 3+ Luminescence intensity graph under solution conditions; Fig.10 It is Fe 3+ Stern-Volmer fitting diagram of solution titration; Fig.11 is a histogram of the luminescence intensity of the metal-organic framework of the present invention in different anion solutions; Fig.12 The metal-organic framework of the present invention has different concentrations of Cr2O7 2- Luminescence intensity graph under solution conditions; Fig.13 The metal-organic framework of the present invention has different concentrations of CrO4 2- Luminescence intensity graph under solution conditions; Fig.14 It is Cr2O7 2- Stern-Volmer fitting diagram of solution titration; Fig.15 It is CrO4 2- Stern-Volmer fitting plot of solution titration. DETAILED DESCRIPTION
[0019] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0020] The invention provides a linear pyridine tetracarboxylic acid ligand Zn (II) based metal-organic framework material, the chemical formula of which is {[Zn2 (L) (5-ATZ)]·1.5DMF·H2O} n , L 4- It is the deprotonated organic ligand (2,5-di-(3,5-dicarboxyphenyl))pyridine (H4L).
[0021] {[Zn2(L)(5-ATZ)]·1.5DMF·H2O} n The crystal structure belongs to the orthorhombic system. Imma Space group, unit cell parameters are: a = 19.038(14) Å, b = 26.520(19) Å, c = 17.040(12) Å, α = β = γ = 90°.
[0022] {[Zn2(L)(5-ATZ)]·1.5DMF·H2O} n One asymmetric unit contains a Zn 2+ ion, half a ligand and half an aminotetrazolyl. Zn1 and three L 4- The four oxygen atoms of the ligand and the nitrogen atom of the aminotetrazolyl form a five-coordinated tetrahedral geometry. 4- There are two coordination modes of carboxylic acid oxygen atoms in the ligand, μ1-η 1 and μ1-η 2 Two Zn1(Ⅱ) ions form a binuclear structural unit, each L 4- The ligand forms a three-dimensional framework structure with pores by connecting four nearby binuclear structural units.
[0023] Among them, the organic ligand is a rigid pyridine tetracarboxylic acid ligand (2,5-di-(3,5-dicarboxyphenyl))pyridine (H4L), and the chemical structure is as follows:
[0024] The ligand is a rigid linear structure containing four carboxylic acid functional groups and a pyridine nitrogen atom, and the four carboxylic acids are located at the meta position of the outer benzene ring.
[0025] The present invention provides a method for preparing a Zn(II)-based metal-organic framework material based on pyridinetetracarboxylic acid ligand, which is specifically implemented in the following manner: Under sealed conditions, the organic ligand (2,5-di-(3,5-dicarboxyphenyl))pyridine (H4L) reacted with the auxiliary ligand aminotetrazolyl CH3N5 (5-ATZ) and zinc nitrate Zn(NO3)2·6H2O in a mixed solution of N,N-dimethylformamide (DMF) and HNO3 to obtain colorless crystals through solvothermal reaction.
[0026] The molar ratio of the organic ligand (2,5-di-(3,5-dicarboxyphenyl))pyridine, the auxiliary ligand aminotetrazolyl and zinc nitrate Zn(NO3)2·6H2O is 3:5:8, and every 0.04 mmol of zinc nitrate corresponds to 2-6 mL of DMF and 1-4 mL of HNO3 (1 mL of HNO3 is dissolved in 10 mL of distilled water). The temperature of the solvothermal reaction is 90-130 °C, and the reaction time is 24-60 hours.
[0027] The invention provides the application of a linear pyridinetetracarboxylic acid ligand-based metal organic framework in gas adsorption and separation and heavy metal ion fluorescence detection.
[0028] The bifunctional metal-organic framework material based on pyridine tetracarboxylic acid ligands and its preparation method and application have excellent stability and can show excellent gas adsorption and separation and heavy metal ion fluorescence detection performance. The separation ratios of mixed gases C2H2 / CO2 and CO2 / CH4 are 5.32 and 17.2 respectively, and the separation ratios of Fe 3+ 、Cr2O7 2- and CrO4 2- The detection limit reached 10 -4 M, which exceeds most existing MOFs materials. The present invention opens up new design and synthesis prospects for novel linear pyridine tetracarboxylic acid ligand-based functional metal organic frameworks and can be used in gas pollution and water pollution.
[0029] Example 1 Weigh the ligand H4L (6 mg, 0.015 mmol), Zn(NO3)3·6H2O (12 mg, 0.04 mmol), and 5-ATZ (1.7 mg, 0.025 mmol) in a 25 mL glass bottle, add DMF (2 mL) and HNO3 (1 mL) (1 mL HNO3 is dissolved in 10 mL distilled water), and ultrasonicate for 30 min to completely dissolve it. Then put it in a 90 ℃ oven for 24 hours. Then cool it to room temperature at 10 ℃ / h to obtain colorless crystals, rinse with DMF solution, and collect by filtration.
[0030] Example 2 Weigh the ligand H4L (6 mg, 0.015 mmol), Zn(NO3)3·6H2O (12 mg, 0.04 mmol), and 5-ATZ (1.7 mg, 0.025 mmol) in a 25 mL glass bottle, add DMF (3.5 mL) and HNO3 (2.5 mL) (1 mL HNO3 is dissolved in 10 mL distilled water), and ultrasonicate for 30 min to completely dissolve it. Then put it in a 110 ℃ oven for 36 hours. Then cool it down to room temperature at 10 ℃ / h to obtain colorless crystals, rinse with DMF solution, and collect by filtration.
[0031] Example 3 Weigh the ligand H4L (6 mg, 0.015 mmol), Zn(NO3)3·6H2O (12 mg, 0.04 mmol), and 5-ATZ (1.7 mg, 0.02 mmol) in a 25 mL glass bottle, add DMF (6 mL) and HNO3 (4 mL) (1 mL HNO3 dissolved in 10 mL distilled water), and sonicate for 30 min to completely dissolve it. Then put it in a 130 ℃ oven for 60 hours. Then cool it down to room temperature at 10 ℃ / h to obtain colorless crystals, rinse with DMF solution, and collect by filtration.
[0032] Example 4 Weigh the ligand H4L (6 mg, 0.015 mmol), Zn(NO3)3·6H2O (12 mg, 0.04 mmol), and 5-ATZ (1.7 mg, 0.02 mmol) in a 25 mL glass bottle, add DMF (4 mL) and HNO3 (1.5 mL) (1 mL HNO3 is dissolved in 10 mL distilled water), and ultrasonicate for 30 min to completely dissolve it. Then put it in a 100 ℃ oven for 30 hours. Then cool it down to room temperature at 10 ℃ / h to obtain colorless crystals, rinse with DMF solution, and collect by filtration.
[0033] Example 5 Weigh the ligand H4L (6 mg, 0.015 mmol), Zn(NO3)3·6H2O (12 mg, 0.04 mmol), and 5-ATZ (1.7 mg, 0.02 mmol) in a 25 mL glass bottle, add DMF (5 mL) and HNO3 (2 mL) (1 mL HNO3 dissolved in 10 mL distilled water), and sonicate for 30 min to completely dissolve it. Then put it in a 120 ℃ oven for 40 hours. Then cool it down to room temperature at 10 ℃ / h to obtain colorless crystals, rinse with DMF solution, and collect by filtration.
[0034] Example 6 Weigh the ligand H4L (6 mg, 0.015 mmol), Zn(NO3)3·6H2O (12 mg, 0.04 mmol), and 5-ATZ (1.7 mg, 0.02 mmol) in a 25 mL glass bottle, add DMF (5.5 mL) and HNO3 (3 mL) (1 mL HNO3 is dissolved in 10 mL distilled water), and ultrasonicate for 30 min to completely dissolve it. Then put it in a 115 ℃ oven for 50 hours. Then cool it down to room temperature at 10 ℃ / h to obtain colorless crystals, rinse with DMF solution, and collect by filtration.
[0035] The test results of the products obtained in Examples 1 to 6 are the same, as shown below: (1) Determination of crystal structure: Select a crystal of suitable shape and size, place it on a single crystal diffractometer, and use a Mo-Kα light source (λ=1.149 Å) to scan and collect crystal diffraction data. Then use SHELXTL-2014 software to refine the data and obtain the structure of the crystal. See the structure diagram Figures 1 to 4 The crystallographic data are shown in Table 1. The property test diagram is shown in Figures 5 to 15 .
[0036] Table 1 Crystallographic data of metal-organic framework materials
[0037] like Figure 1 As shown, an asymmetric unit of the metal-organic framework material includes a Zn 2+ ion, half a ligand, and half an aminotetrazolium.
[0038] like Figure 2 As shown, Zn1 and L from three 4- The four oxygen atoms of the ligand and the nitrogen atom of the aminotetrazolyl form a five-coordinated tetrahedral geometry. The two Zn1(Ⅱ) ions form a binuclear structural unit.
[0039] like Figure 3 As shown, in the metal-organic framework, a part of L 4- The four carboxyl groups in the ligand remove four protons and connect to four Zn(Ⅱ) ions in the form of bidentate chelation. 4- The four carboxyl groups in the ligand remove four protons and connect to eight Zn(Ⅱ) ions in the form of a monodentate bridge.
[0040] like Figure 4 As shown, each L in the metal-organic framework 4- The ligand forms a three-dimensional framework structure with pores by connecting four nearby binuclear structural units.
[0041] like Figure 5 As shown in the figure, the N2 adsorption performance test of the metal-organic framework at 77 K is shown in the figure. The N2 adsorption isotherm of the metal-organic framework (the inset shows the pore size distribution). It can be seen that its adsorption isotherm type is reversible micropores (type I), and the maximum N2 adsorption capacity is 80.71 cm 3 / g. From the pore size distribution curve in the inset, it can be seen that the pore size is mainly distributed at 7.33 Å.
[0042] like Figure 6 As shown in the figure, the C2H2, CO2 and CH4 adsorption performance test of the metal-organic framework at 273 K and 298 K, as shown in the figure, is the C2H2, CO2 and CH4 adsorption performance test of the metal-organic framework at 273 K and 298 K, including the C2H2, CO2 and CH4 adsorption isotherms of the metal-organic framework. It can be seen that at 1 atm, 273 K and 298 K, the adsorption amount of C2H2 by the metal-organic framework is 47.64 cm 3 / g and 35.89 cm 3 / g; the adsorption capacity for CO2 is 43.35 cm 3 / g and 28.37 cm 3 / g; the adsorption capacity for CH4 was 17.43 cm 3 / g and 8.11 cm 3 / g. This shows that there are differences in the adsorption of C2H2, CO2 and CH4 by metal-organic frameworks.
[0043] like Figure 7 As shown in the figure, the separation ratio of CO2 / CH4 and C2H2 / CO2 of the metal organic framework at 298 K. The figure is a separation ratio curve of CO2 / CH4 and C2H2 / CO2 of the metal organic framework at 298 K. It can be seen that when the molar ratio of the mixed gas C2H2 / CO2 and CO2 / CH4 is 50:50, the separation ratios are 5.32 and 17.2 respectively, indicating that the separation effect is relatively good.
[0044] like Figure 8 As shown in the figure, the fluorescence performance of the metal-organic framework was tested in different cation solutions with a concentration of 0.01 mol / L. The figure is a histogram of the fluorescence intensity of the metal-organic framework in different metal ion solutions with a concentration of 0.01 mol / L. It can be seen that K + 、Al 3+ Compared with the blank group, the fluorescence intensity did not change much. 2+ , Li + Mg 2+ 、Na + 、Zn 2+ 、Ni2+ The fluorescence intensity of the suspensions decreased to varying degrees, while Fe 3+ It produced an obvious quenching phenomenon, indicating that the metal-organic framework material can selectively recognize and detect Fe 3+ .
[0045] like Fig. 9 As shown, the metal-organic framework is 3+ Titration test under the condition of solution concentration of 0.01 mol / L. The figure shows the metal-organic framework at different concentrations of Fe 3+ Luminescence intensity diagram of emission peak under ion solution conditions. It can be seen that with the increase of Fe 3+ As the concentration increases, the fluorescence intensity in the solution gradually decreases. 3+ When the concentration reached 120 μL (0.38 mM), the fluorescence of the metal-organic framework was quenched, and the quenching rate reached 96%, indicating a good quenching effect.
[0046] like Fig.10 As shown, the metal-organic framework is 3+ The relative fluorescence intensity of the solution at low concentrations is related to Fe 3+ The concentration relationship diagram is shown in the figure, which shows the metal-organic framework in Fe 3+ The relative fluorescence intensity of the solution at low concentrations is related to Fe 3+ The concentration relationship diagram is the Stern-Volmer fitting diagram of the metal organic framework. It can be seen that when the concentration is low, the relative fluorescence intensity of the solution is 3+ The concentration of has a good linear relationship, and there will be a certain deviation when the concentration is high, indicating that quenching is a process that exists both statically and dynamically. It can be obtained that K sv The value is 2.94×10 4 M -1 , for Fe 3+ The detection limit was 1.67×10 -4 M, the detection limit is low, indicating that the metal-organic framework material has a strong affinity for Fe 3+ The detection has higher sensitivity.
[0047] like Fig.11 As shown, the fluorescence performance of the metal-organic framework was tested in different anion solutions with a concentration of 0.01 mol / L. The figure is a histogram of the fluorescence intensity of the metal-organic framework in different anion solutions with a concentration of 0.01 mol / L. It can be seen that SO4 2- , Cl - 、CO3 2- There is almost no effect on the fluorescence intensity. - ,I - 、C2O4 2-For the phenomenon of reduced fluorescence, Cr2O7 2- 、CrO4 2- There is an obvious quenching phenomenon of its fluorescence, indicating that the metal-organic framework material can selectively identify and detect Cr2O7 2- and CrO4 2- .
[0048] like Fig.12 As shown, the metal-organic framework in Cr2O7 2- The titration experiment was conducted under the condition of solution concentration of 0.01 mol / L. The figure shows the metal-organic framework at different concentrations of Cr2O7 2- Luminescence intensity diagram of emission peak under ion solution conditions. It can be seen that with the increase of Cr2O7 2- The fluorescence intensity gradually decreases with the addition of Cr2O7 2 When the concentration reached 120 μL (0.38 mM), fluorescence quenching occurred, and the quenching rate reached 96%, indicating a good quenching effect.
[0049] like Fig.13 As shown, the metal-organic framework in CrO4 2- The titration experiment was conducted under the condition of solution concentration of 0.01 mol / L. The figure shows the metal-organic framework at different concentrations of CrO4 2- Luminescence intensity diagram of emission peak under ion solution conditions. It can be seen that with the increase of CrO4 2- The fluorescence intensity gradually decreases with the addition of CrO4 2- When the concentration reached 240 μL (0.74 mM), fluorescence quenching occurred, and the quenching rate reached 95.3%, indicating a good quenching effect.
[0050] like Fig.14 As shown, the metal-organic framework in Cr2O7 2- The relative fluorescence intensity of the solution at low concentration is similar to that of Cr2O7 2- Concentration relationship diagram, as shown in the figure, metal-organic framework in Cr2O7 2- The relative fluorescence intensity of the solution at low concentration is similar to that of Cr2O7 2- The concentration relationship diagram is the Stern-Volmer fitting diagram of the metal-organic framework. It can be seen that when the concentration is low, the relative fluorescence intensity of the solution is 3+ The concentration of has a good linear relationship. sv The value is 2.17×10 4 M -1 , for Cr2O7 2- The detection limit is 4×10 -4 M, the detection limit is low, indicating that the metal-organic framework material has good 2-The detection has higher sensitivity.
[0051] like Fig.15 As shown, the metal-organic framework in CrO4 2- The relative fluorescence intensity of the solution at low concentrations is related to CrO4 2- Concentration relationship diagram, as shown in the figure, metal-organic framework in CrO4 2- The relative fluorescence intensity of the solution at low concentrations is related to CrO4 2- The concentration relationship diagram is the Stern-Volmer fitting diagram of the metal-organic framework. It can be seen that when the concentration is low, the relative fluorescence intensity of the solution is 3+ The concentration of has a good linear correlation. sv The value is 7.36×10 3 M -1 , for CrO4 2- The detection limit was 6.3×10 -4 The detection limit of M is low, indicating that the metal-organic framework material has good stability to CrO4 2- The detection has higher sensitivity.
Claims
1. A bifunctional metal-organic framework material based on pyridinetetracarboxylic acid ligands, characterized in that: The chemical formula is {[Zn2(L)(5-ATZ)]·1.5DMF·H2O} n , L 4- It is a deprotonated organic ligand (2,5-di-(3,5-dicarboxyphenyl))pyridine.
2. The bifunctional metal-organic framework material based on pyridinetetracarboxylic acid ligand according to claim 1, characterized in that: The {[Zn2(L)(5-ATZ)]·1.5DMF·H2O} n The crystal structure belongs to the orthorhombic system. Imma Space group, unit cell parameters are: a = 19.038(14) Å, b = 26.520(19) Å, c = 17.040(12) Å, α = β = γ =90°.
3. The bifunctional metal-organic framework material based on pyridinetetracarboxylic acid ligand according to claim 1, characterized in that: The {[Zn2(L)(5-ATZ)]·1.5DMF·H2O} n One asymmetric unit contains a Zn 2+ ion, half ligand and half aminotetrazolyl; Zn1 and from three L 4- The four oxygen atoms of the ligand and the nitrogen atom on the aminotetrazolyl form a five-coordinated tetrahedral geometry; L 4- There are two coordination modes of carboxylic acid oxygen atoms in the ligand, μ1-η 1 and μ1-η 2 ; Two Zn1(Ⅱ) ions form a binuclear structural unit, each L 4- The ligand forms a three-dimensional framework structure with pores by connecting four nearby binuclear structural units.
4. The bifunctional metal-organic framework material based on pyridinetetracarboxylic acid ligand according to claim 1, characterized in that: The organic ligand (2,5-di-(3,5-dicarboxyphenyl))pyridine is a rigid linear structure, comprising four carboxylic acid functional groups and one pyridine nitrogen atom, wherein the four carboxylic acids are located at the meta position of the outer benzene ring.
5. The bifunctional metal-organic framework material based on pyridinetetracarboxylic acid ligand according to claim 4, characterized in that: The chemical structural formula of the organic ligand (2,5-di-(3,5-dicarboxyphenyl))pyridine is: 。 6. The method for preparing a bifunctional metal-organic framework material based on pyridinetetracarboxylic acid ligand according to claim 1, characterized in that: Under sealed conditions, the organic ligand (2,5-di-(3,5-dicarboxyphenyl))pyridine reacts with aminotetrazole and zinc nitrate hexahydrate in a mixed solution of N,N-dimethylformamide and nitric acid to obtain colorless crystals through solvothermal reaction.
7. The method for preparing a bifunctional metal-organic framework material based on pyridinetetracarboxylic acid ligand according to claim 6, characterized in that: The molar ratio of the organic ligand (2,5-di-(3,5-dicarboxyphenyl))pyridine, aminotetrazolyl and zinc nitrate hexahydrate is 3:5:8, and every 0.04 mmol of zinc nitrate hexahydrate corresponds to 2-4 mL of N,N-dimethylformamide and 1-4 mL of nitric acid, wherein the concentration of nitric acid is 1 mL of HNO3 dissolved in 10 mL of distilled water.
8. The method for preparing a bifunctional metal-organic framework material based on pyridinetetracarboxylic acid ligand according to claim 6, characterized in that: The temperature of the solvent thermal reaction is 90-130° C. and the time is 24-60 hours.
9. Application of bifunctional metal-organic framework materials based on pyridinetetracarboxylic acid ligands, characterized in that: The bifunctional metal-organic framework material based on pyridinetetracarboxylic acid ligands according to any one of claims 1 to 8 is used as a material for the adsorption separation of CO2 / CH4 and C2H2 / CO2.
10. Application of bifunctional metal-organic framework materials based on pyridinetetracarboxylic acid ligands, characterized in that: The bifunctional metal-organic framework material based on pyridine tetracarboxylic acid ligand according to any one of claims 1 to 8 is used as a Fe 3+ 、Cr2O7 2- and CrO4 2- Highly sensitive fluorescent detection material.
Citation Information
Patent Citations
Zn-MOF fluorescent-sensing material and preparation method thereof
CN107602596A
Metal organic framework material, preparation thereof and application of metal organic framework material in rapid response to hydrogen chloride gas
CN114181399A
Metal-organic framework material based on tricarboxylic acid pyridine ligand, preparation method and application
CN117843974A
Water stable zinc-based metal organic framework and method of use
US20200190114A1